Fe-Ni invar alloy: an example of fractal decomposition? - Abromeit, C.; Ananthakrishna, G. (Вопросы атомной науки и техники, 2005)
The important experimental results of irradiated and unirradiated Ni-Fe alloys and some approaches to explain the various contradictory behaviours are discussed. We outline the known results of the scattering experiments and suggest possible directions for theoretical investigations to explain the decomposition kinetics of the FeNi Invar alloy.